The case for Corona bonds - Matej Avbelj; Antonia Baraggia; Jürgen Bast; Bojan Bugaric; Emanuel Castellarin; Francesco Costamagna; Anuscheh Farahat; Matthias Goldmann; Anna Katharina Mangold; Mario Savino; Alexander Thiele; Annamaria Viterbo (Leibniz Institute for Financial Research SAFE, 2020)
Corona bonds are feasible and important to preserve the European project. We set out a number of principles that might serve as a blueprint for the European institutions. Importantly, Corona bonds could be issued through a new public law entity and include all the safeguards required for the protection of the fundamental values of the EU. This proposal is pragmatic in the sense that it facilitates the choice European leaders have to make now; necessary to secure the resilience of the European Union. The political risks are significantly higher now than in 2010. The gargantuan challenge of tackling the combined impact of climate change, migration, digitalization, geopolitical shifts, and the spread of autocracy, requires leadership and joint action by the Council and the Eurogroup.
Keywords: 330; Corona Bonds; Coronavirus